ISLAMIC COUNSELING GUIDANCE STRATEGIES IN OVERCOMING SMOKING BEHAVIOR IN JUNIOR HIGH SCHOOL STUDENTS - Anaa lillah; Fitriah M. Suud (Jurnal Konseling Pendidikan Islam, 2026)
Smoking behavior is a reprehensible behavior that impacts physical, mental, and spiritual health, the increasing number of smokers at an early age, especially early adolescence, namely junior high school students, is a concern for the education of the younger generation. This study aims to analyze smoking behavior in junior high school students and examine the appropriate Islamic guidance and counseling strategies in addressing student smoking behavior in schools. This study uses a qualitative method with a case study approach, involving junior high school students who have smoking behavior, guidance and counseling teachers and parents. Data were collected through in-depth interviews, observations, and documentation studies. The results of the study identified two main problem formulations: first, the phenomenon of smoking behavior in junior high school students in Yogyakarta. The percentage of students who smoke is concerning, the beginning of smoking at a very young age, the influence of parents and peers on smoking behavior that is associated with modeling theory and self-efficacy theory. Second, it explains the strategies of Islamic guidance and counseling teachers in dealing with student smoking behavior which include three main approaches: supervision through routine raids 20%, discussion group counseling 35%, and educational and spiritual discipline development 45%. Educational and spiritual discipline development, instilling the values ​​of the Quran and Hadith, is considered the most effective way to foster long-term self-awareness. These strategies are considered to have an impact on preventing and addressing smoking behavior in adolescents.